Analysis of Predictors of Relapse in Children with Steroid Sensitive Nephrotic Syndrome - Bhatta, Mukesh; Shah, Gauri Shankar; Mishra, Om Prakash (Journal of Nepal Paediatric Society, 2017)
Introduction: Children with idiopathic nephrotic syndrome (INS) are steroid responsive but have relapses in subsequent non-treatment period. The objective of the present study was to analyze the factors which could predict relapses in these children. Material and Methods: Forty patients of INS aged 1-14 years of both gender were enrolled over one year period and followed for six months after treatment of initial episode of Nephrotic Syndrome. Results: The median age of children was 4.5 years and male to female ratio 1.9:1. There were 24(60%) relapses and 16(40%) non-relapses. The relapses had significantly higher mean total leukocyte count, serum urea, potassium and cholesterol than non-relapses. It was also observed that the median age of onset in relapses was significantly lower than non-relapses (p<0.001). Also, the median time to response to steroid therapy was longer in relapses than non-relapses (p<0.001). Children who relapsed had infections at the time of relapse. Conclusion: Thus, onset of disease in younger age group, late response to steroid therapy and presence of infections were found to be associated with relapses in these children.